Networking as a Word of Mouth Marketing Strategy in Entrepreneurial Contexts (2018)
The purpose of this research is to create a Network Marketing Model (NMM) for entrepreneurs relying on networking activities to activate Word of Mouth processes. In order to achieve this, we support our theoretical findings in three pillars: Entrepreneurial Marketing (EM), networking activities, and Word of Mouth Marketing (WOMM). These 3 frameworks are explained in Chapters 1 - 2. Additionally, this thesis addresses two relevant concerns in the area of EM and WOMM: the influence of social networks and the actors in WOM processes in an entrepreneurial context. These issues are developed through simulations using Agent-Based Modeling in Chapter 3 and an empirical experiment in Chapter 4. Finally, Chapter 5 proposes the NMM according to the main findings of previous sections